New Solitary Wave Patterns of the Fokas System in Fiber Optics - Kaplan, Melike; Akbulut, Arzu; Alqahtani, Rubayyi T. (MDPI AG, 2023)
The Fokas system, which models wave dynamics using a single model of fiber optics, is the design under discussion in this study. Different types of solitary wave solutions are obtained by utilizing generalized Kudryashov (GKP) and modified Kudryashov procedures (MKP). These novel concepts make use of symbolic computations to come up with a dynamic and powerful mathematical approach for dealing with a variety of nonlinear wave situations. The results obtained in this paper are original and have the potential to be useful in mathematical physics.
Keywords: modified Kudryashov procedure; QA1-939; exact solutions; generalized Kudryashov method; exact solutions; modified Kudryashov procedure; generalized Kudryashov method; symbolic computation; symbolic computation; Mathematics